MCRS1 is essential for epiblast development during early mouse embryogenesis. Issue 1 (January 2020) - Cui, Wei; Cheong, Agnes; Wang, Yongsheng; Tsuchida, Yuran; Liu, Yong; Tremblay, Kimberly D; Mager, Jesse
Abstract : Microspherule protein 1 (MCRS1, also known as MSP58) is an evolutionarily conserved protein that has been implicated in various biological processes. Although a variety of functions have been attributed to MCRS1 in vitro, mammalian MCRS1 has not been studied in vivo . Here we report that MCRS1 is essential during early murine development. Mcrs1 mutant embryos exhibit normal morphology at the blastocyst stage but cannot be recovered at gastrulation, suggesting an implantation failure. Outgrowth (OG) assays reveal that mutant blastocysts do not form a typical inner cell mass (ICM) colony, the source of embryonic stem cells (ESCs). Surprisingly, cell death and histone H4 acetylation analysis reveal that apoptosis and global H4 acetylation are normal in mutant blastocysts. However, analysis of lineage specification reveals that while the trophoblast and primitive endoderm are properly specified, the epiblast lineage is compromised and exhibits a severe reduction in cell number. In summary, our study demonstrates the indispensable role of MCRS1 in epiblast development during early mammalian embryogenesis.